2021
DOI: 10.1089/jpm.2020.0622
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Lidocaine for Complex Cancer Pain in the Home or Inpatient Hospice Setting: A Review and Synthesis of the Evidence

Abstract: Background: Cancer pain can remain refractory despite escalating opioids and adjuvants. Systemic Lidocaine is an option, but current approaches are hospital centered. While advantageous in advanced cancer, evidence is lacking for parenteral Lidocaine use in community-based care. Objectives: Review evidence for parenteral lidocaine in complex cancer pain outside the hospital setting. Design: Systematic review of peer-reviewed articles of any s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Another challenge is the lack of a standardized and unified way to measure pain. One review of the literature recognized that none of the articles analyzed used a validated measure of pain [ 47 ]. While each of the mentioned articles acknowledges that lidocaine did effectively reduce pain scores in whichever way they were measured, it is important moving forward to have an established and validated measure of pain, especially in pediatric patients who may not be able to verbalize their discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge is the lack of a standardized and unified way to measure pain. One review of the literature recognized that none of the articles analyzed used a validated measure of pain [ 47 ]. While each of the mentioned articles acknowledges that lidocaine did effectively reduce pain scores in whichever way they were measured, it is important moving forward to have an established and validated measure of pain, especially in pediatric patients who may not be able to verbalize their discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review was published evaluating articles with a combined seventy-three total patients who were treated with lidocaine parenterally for their complex, cancer-related pain [ 47 ]. Among the articles included in the review, there was no consensus on validated outcome measures that can be used to compare pain between treatment groups.…”
Section: Systemic Lidocaine Infusions In Patients With Cancermentioning
confidence: 99%
“…Continuous intravenous administration of lidocaine during and after abdominal surgery improves patient rehabilitation and shortens hospital stay [15]. The analgesic synergy between topical lidocaine and topical opioids morphine, levorphanol and buprenorphine has been found [16]; opioid-free anesthesia with lidocaine and infusions may be an alternative technique for laparoscopic cholecystectomy especially in patients with high risk for postoperative nausea and vomiting [17]; lidocaine infusion can improve pain relief and physical function in opioid dependent patients, thus improving compliance and patient satisfaction, which may potentially help wean patients off narcotics [18]; analysis of literature data showed that parenteral administration of lidocaine can be effective and safe when cancer pain becomes refractory despite escalating opioids and adjuvants [19].…”
Section: Lidocainementioning
confidence: 99%
“…In addition to its analgesic properties, lidocaine exhibits anti-oncogenic and anti-inflammatory effects through various pathways ( 61 64 ). Dozens of laboratory studies have been performed to flesh out the biological pathways responsible for lidocaine’s observed effects ( 12 , 13 , 32 , 65 68 ). Unfortunately, clinical data including retrospective analyses are sparce.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…It is important to remember that using intravenous lidocaine as an analgesic is off-label. To date there have been no studies to show that lidocaine infusions are harmful to cancer patients so long as they are employed judiciously and there are no contraindications or conditions that would increase toxicity, such as severe liver disease or low protein states ( 32 , 60 , 61 , 71 ). Centers using intravenous lidocaine infusions should have safety protocols and dosing guidelines to avoid harm in patients receiving this treatment ( 60 ).…”
Section: Local Anestheticsmentioning
confidence: 99%